Recent Advances in Biological Functions of Thick Pili in the Cyanobacterium Synechocystis sp. PCC 6803 - Chen, Zhuo; Li, Xitong; Tan, Xiaoming; Zhang, Yan; Wang, Baoshan (Frontiers in Plant Science, 2020)
Cyanobacteria have evolved various strategies to sense and adapt to biotic and abiotic stresses including active movement. Motility in cyanobacteria utilizing the type IV pili (TFP) is useful to cope with changing environmental conditions. The model cyanobacterium Synechocystis sp. PCC 6803 (hereafter named Synechocystis) exhibits motility via TFP called thick pili, and uses it to seek out favorable light/nutrition or escape from unfavorable conditions. Recently, a number of studies on Synechocystis thick pili have been undertaken. Molecular approaches support the role of the pilin in motility, cell adhesion, metal utilization, and natural competence in Synechocystis. This review summarizes the most recent studies on the function of thick pili as well as their formation and regulation in this cyanobacterium.